Understanding Business ( Kèm Đĩa CD-ROM) - Nickels William G (Irwin/McGraw Hill, 2003)
This multi-cassette abridged version of the UB6E allows students to brush up on business concepts while commuting, jogging, or wherever/whenever is most convenient. --This text refers to the Audio Cassette edition.